Manajemen Pendidikan di Pondok Pesantren - Muhammad Sholeh (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2022)
Islamic boarding schools with their diversity include educational institutions or organizations that areunique in terms of educational management. Both in terms of leadership, management of education thatuses Islamic principles, to activities that support the implementation of education in Islamic boardingschools have their own characteristics. This training will be given to all managers of the TahfidzulQur'an Islamic Boarding School Fathul Huda Blitar. This Islamic Boarding School is a partner of PKMactivities because the Tahfidzul Qur'an Fathul Huda Islamic Boarding School Blitar has good potentialand is able to be competed with other Islamic Boarding Schools, but its human resources still havelimited knowledge and skills in the field of education management science.